PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP COMPANY PERFORMANCE PADA PERUSAHAAN MANUFAKTUR DI INDONESIA DAN THAILAND - DOLFIN ENGELBERT GIOVANI; RICKY A. MULYANA (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2017)
The purpose of this study is to obtain empirical evidence and to test the factors that affect company performance between Indonesia and Thailand, by using ownership concentration, managerial ownership, institutional ownership, board size, audit committee, audit type, firm size, financial leverage, and firm age variables. The firm performance is measured by using Tobin’s Q. Population of this study is the manufacturing companies listed in Indonesia Stock Exchange (IDX) and Stock Exchange Thailand (SET) during 2013 to 2015. The sample is obtained by using purposive sampling method. There are 129 samples from Indonesia, and 165 samples from Thailand selected as the final samples. Hypotheses tested by using multiple regression analysis. The result of this studies indicates that board size and firm age shows impact to company performance in both country, Indonesia and Thailand. But ownership concentration, managerial ownership, institutional ownership, audit committee, audit type, firm size, and financial leverage do not have impact on company performance in Indonesia and Thailand.